Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules27196187
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Is a Primary Antioxidant in Mammals

Abstract: Ascorbate (vitamin C in primates) functions as a cofactor for a number of enzymatic reactions represented by prolyl hydroxylases and as an antioxidant due to its ability to donate electrons, which is mostly accomplished through non-enzymatic reaction in mammals. Ascorbate directly reacts with radical species and is converted to ascorbyl radical followed by dehydroascorbate. Ambiguities in physiological relevance of ascorbate observed during in vivo situations could be attributed in part to presence of other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 225 publications
0
5
0
Order By: Relevance
“…The results imply that SOD3 was produced by the homed cells and protected the irradiated tissues including bone marrow through the scavenging of superoxide by SOD3. Since Asc also effectively scavenges radicals including superoxide [7,8], it is thought that HSCs were protected from the cytotoxic effects of oxygen radicals by Asc in our study.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The results imply that SOD3 was produced by the homed cells and protected the irradiated tissues including bone marrow through the scavenging of superoxide by SOD3. Since Asc also effectively scavenges radicals including superoxide [7,8], it is thought that HSCs were protected from the cytotoxic effects of oxygen radicals by Asc in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Since the replenishment of Asc leads to a decreased glucocorticoid response in humans and in animal models after exposure to a psychological or physical stressors [50], Asc likely acts to suppress the injurious effects of the glucocorticoid that is released under stress conditions. Because Asc is a potent antioxidant, scavenging oxygen radicals with electron donation [7,8], the primary action of Asc appears to be that of protecting BMCs against ROS that are produced by ionizing radiation and by corticosterone response. Since Asc exerts pleiotropic functions, it is also possible that Asc stimulates the hematopoietic process by supporting enzymatic reactions, such as prolyl hydroxylase, or by epigenetically regulating gene expression [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 18 19 Given this logic the clinical trial reported here was designed to rapidly restore vitamin C following transplantation and utilize its endothelial stabilizing effect to reduce the impact of mucosal and endothelial injury post-transplant. 20 21 Ameliorating the tissue injury in turn would modulate the inflammatory milieu, potentially mitigating alloantigen presentation in the early days following transplant, eventually reducing GVHD likelihood evolving from recovering donor derived T cells. This concept is supported here by the observed trend toward reduced acute GVHD (grade II-IV) and chronic GVHD in Vitamin C recipients, as visualized in the graph analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate (vitamin C) is an essential micronutrient in primates and serves as an antioxidant and a cofactor for various enzymatic activities represented by prolyl hydroxylases ( Fujii et al, 2022 ). Because the induction of glycolysis by mTOR is mediated by the activation of HIF1-α and stimulation of glycolytic enzymes and ascorbate inhibits HIF-1α expression, it inhibits training immune in a dose-dependent manner ( Cheng et al, 2014 ).…”
Section: Inhibitors Of Targeting Trained Immunitymentioning
confidence: 99%